Societal Sources of Negative Attitudes Against The Roma: The Case of Romania - Eliza Markley; Darina Lepadatu (Journal of Global Initiatives, 2012)
Romania is the home of one of the largest Roma minorities in the world. This paper examined sources of negative attitudes toward the Roma in Romania by testing two explanations, that of societal integration and contact on a nationally representative sample. Our findings suggest that the negative attitudes against the Roma are largely driven by the type of relationships and contact that Romanians develop with the Roma. Having Roma in the family or as friends or colleagues at work decreases Romanians ' negative attitudes against the Roma. On the contrary, as the contact theory states, being in limited contact with them, without engaging in personal relationships is conducive of suspicion, hostility, and negative attitudes. Second, the interpersonal level of individuals' trust contributes significantly to building positive attitudes toward the Roma. Consequently, we recommend that future global initiatives and strategies on Roma inclusion should be centered on increasing the level of interpersonal trust and contact between Roma and non-Roma.